Effects of trichothecene mycotoxin T-2 toxin on haematological and immunological parameters of rainbow trout (Oncorhynchus mykiss) - Modra, Helena; Palikova, Miroslava; Hyrsl, Pavel; Bartonkova, Jana; Papezikova, Ivana; Svobodova, Zdenka; Blahova, Jana; Mares, Jan (Mycotoxin research, 2020)
The aim of this study was to assess the effects of T-2 toxin-contaminated feed (at concentrations of 1.0 and 1.8 mg/kg) on the rainbow trout immune system by studying non-specific cellular and humoral immune responses and its effect on red and white blood cells. Consumption of T-2 toxin at both concentrations resulted in significantly increased erythrocyte counts and a decrease in mean corpuscular volume. While a significant decrease in mean corpuscular haemoglobin was observed at both experimental concentrations, the decrease in plasma haemoglobin was only significant at the higher T-2 toxin concentration. Higher T-2 toxin concentrations resulted in a significant increase in leukocyte and lymphocyte count, while absolute phagocyte count and counts of less mature neutrophil granulocyte forms remained unchanged at both concentrations. Non-specific humoral immunity (bactericidal activity measured as complement activation) decreased significantly in both experimental groups when compared with the control. The results of this study show that T-2 toxin in feed at a concentration range of 1.0-1.8 mg/kg influences the immunological defence mechanisms of rainbow trout.Trial registration number, MSMT-3876/2014-14; date of registration, 31/1/2014.
Keywords: Leukocyte Count; Fusarium; Erythrocyte Count; Immunoglobulins; krmivo pro zvířata; Deoxynivalenol; Hemoglobins; Fungi; kontaminace potravin; T-2 toxin; zvířata; počet erytrocytů; Erythropoiesis; humorální imunita; T-2 Toxin; Food Contamination; Immunity, Humoral; hemoglobiny; Animal Feed; počet leukocytů; Oncorhynchus mykiss; Animals